ANALISIS DRAMATURGI PADA REMAJA PENGGUNA APLIKASI TIK-TOK DI DUSUN 1 BUKIT TARAS DESA DELIK KECAMATAN PELALAWAN KABUPATEN PELALAWAN PROVINSI RIAU - Tika Fardila; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research was conducted in Dusun 1 Bukit Taras, Delik Village, Pelalawan District, Pelalawan District, Riau Province. As the purpose of this study is to find out: 1) Front stage impression processing in the use of the tiktok application. 2) Backstage life and use of the tiktok app from a tiktok celeb. Therefore, to achieve this goal, a descriptive qualitative method was used by taking two people as key informants and two people as supporting informants. This study used a purposive sampling technique through observation, interviews and documentation. The results of a study regarding dramaturgical analysis of adolescent users of the tik-tok application. Judging from the impression processing on the front stage that happened to the first key informant and the second key informant both showed the impression presented on the front stage by building trust about the character shown in the eyes of their followers by displaying glamor, humility and sociability. Judging from the life of the back stage and the use of the tiktok application that occurred in the first key informant and the second key informant, there is a difference between what he displays on the front stage and the back stage in the reality of his life. As the two key informants use the social media tiktok according to their interests. As with the first informant who had the desire that he would use his social media tiktok for a platform for existence that would be recognized by other tiktok users and gain popularity. Whereas in the second informant there was a desire for him to take advantage of social media tiktok as a place for existence as well as getting rupiah coffers. Keywords: Dramaturgy, Impression Processing, Tiktokers